Biocompatibility studies of macroscopic fibers made from carbon nanotubes: Implications for carbon nanotube macrostructures in biomedical applications. (March 2021) - Yan, J. Stephen; Orecchioni, Marco; Vitale, Flavia; Coco, Julia A.; Duret, Guillaume; Antonucci, Salvatore; Pamulapati, Sushma Sri; Taylor, Lauren W.; Dewey, Oliver S.; Di Sante, Moises; Segura, Anna Maria; Gurcan, Cansu; et al.
Abstract: Macroscopic carbon nanotube fiber (CNTF) is a continuous monofilament microns-thick thread whose cross section consists of ten to hundreds of millions of tightly packed, aligned carbon nanotubes (CNTs). CNTF is flexible, strong, conductive, and has excellent electrochemical properties, making it an ideal candidate for bioelectronic interfaces. CNTF recent applications range from neuroelectronics and cardiac electrophysiology to biosensors. However, various reports on CNT toxicity have generated confusion on the biosafety of all CNT-based materials despite significant differences among individualized CNTs, unstructured CNT aggregates, and stable CNT macrostructures in compositions and morphologies. Here, the bio- and immune-compatibility profiles of CNTF are systematically evaluated at cellular, organ, and systemic levels. In vitro, CNTF shows good cytocompatibility with cell-lines like HEK-293, SH-SY5Y, as well as primary cardiomyocytes and macrophages. Ex vivo, CNTF shows no impact on blood parameters or functionality of key immune cells. In vivo, intraperitoneal injections of leachates from CNTF production reveal no evidence of toxicity suggesting no leachable or residual degradable byproducts. In addition, as the first multiscale toxicological evaluation of a CNT macrostructure, this report demonstrates that CNT macrostructures should be evaluated as their standalone class of carbon material, separately from individualized CNTs and unstructured CNT agglomerates. Graphical abstract: Image 1